2023
DOI: 10.1177/10998004231194954
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Fatigue Using Electrophysiological Techniques and Non-invasive Brain Stimulation in People With Multiple Sclerosis- A Review and Discussion

Karlie Hamilton,
Katy Smith,
Karen Winn
et al.

Abstract: Objective: The purpose of this literature review article is to provide a synthesis of recent research focused on the use of 3 techniques to evaluate MS-related fatigue: electroencephalography [EEG], transcranial direct-current stimulation (tDSC), and transcranial- magnetic stimulation (TMS). Method: We performed a literature search in the Cumulative Index to Nursing and Allied Health Literature (CINAHL, EBSCOhost), MEDLINE (OVID), APA PsycInfo (OVID), Scopus (Elsevier), and Web of Science (Clarivate) databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(86 reference statements)
0
0
0
Order By: Relevance
“…In addition, numerous studies have found that tDCS is efficacious for motor recovery after stroke [68], especially when combined with other rehabilitation methods [69]. Finally, the preponderance of studies conducted in MS has shown significant effects due to tDCS, with the strongest findings being observed in measurements involving cognitive and physical fatigue [70,71]. In summary, the vast majority of tDCS motor skill and learning studies in every population have involved simple motor tasks, and the findings of the current study suggest that tDCS has the potential to also improve motor learning in complex tasks in populations other than healthy young adults, although perhaps to the same extent as in simple motor tasks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous studies have found that tDCS is efficacious for motor recovery after stroke [68], especially when combined with other rehabilitation methods [69]. Finally, the preponderance of studies conducted in MS has shown significant effects due to tDCS, with the strongest findings being observed in measurements involving cognitive and physical fatigue [70,71]. In summary, the vast majority of tDCS motor skill and learning studies in every population have involved simple motor tasks, and the findings of the current study suggest that tDCS has the potential to also improve motor learning in complex tasks in populations other than healthy young adults, although perhaps to the same extent as in simple motor tasks.…”
Section: Discussionmentioning
confidence: 99%